Exercise science - Glass, Stephen, 1964 January 5-; Hatzel, Brian; Albrecht, Rick, 1952- (--For dummies., 2025)
"Covers must-know information about the how and why to body movement. This useful primer covers content found in a typical introduction course in this topic area--which includes the likes of exercise physiology, biomechanics, and more. With current and helpful guidance, this book includes information on wearable technology, fitness programming across the lifespan, exercise as medicine, and the 101 on human performance, including prevention and care of injuries"--